Rare bird documentation form for Snowy Owl at DeSoto National Wildlife Refuge, 1989 - Starr, Robertet al (1989)
Rare bird documentation form for a Snowy Owl at DeSoto National Wildlife Refuge in Harrison County, IA on December 16, 1989. Epson - sheet feed